Effect of Hemostatic Agents on Shear Bond Strength of Orthodontic Eyelets Bonded with Conventional and Self-etch Adhesives - Arian Hesam Arefi; Seyed Amir Hossein Mirhashemi; Tabassom Hooshmand; Mohammad Javad Kharazi Fard; Mohammad Sadegh Ahmad Akhoundi (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: The risk of debonding of the orthodontic eyelets due to blood contamination from the impacted tooth is a clinical problem that orthodontists face routinely. Purpose: This study aimed to assess the effect of hemostatic agents (Viscostat clear and Astringedent X) on shear bond strength (SBS) of orthodontic eyelets bonded with conventional (Transbond XT) and universal adhesive (GC-G Premio bond) adhesives. Materials and Method: In this experimental study, 84 freshly extracted bovine lower incisors were randomly divided into 7 groups namely TBXT, Blood, SEP, VISCO + TBXT, VISCO + SEP, ASTX + TBXT, and ASTX + SEP groups. In the TBXT group, teeth were etched with phosphoric acid gel, and then, the Transbond XT primer was applied and eyelets were bonded with Transbond XT. In the blood group, first, contamination with blood was done followed by the same procedure as TBXT. In other groups, the teeth were etched with phosphoric acid and based on their group allocation, Transbond XT primer (in TBXT groups), GC-G Premio Bond (in SEP groups), ViscoStat Clear gel (in VISCO groups), or Astringedent X (in ASTX groups) were applied. The SBS was measured for each group and the adhesive remnant index (ARI) was determined. Results: The mean SBS was 20.79 MPa in VISCO+SEP group, 19.2 MPa in the TBXT group, 16.06 MPa in the SEP group, 15.43 MPa in VISCO+TBXT group, 9.39 MPa in AST-X+TBXT group, and 1.62 MPa in the blood group. The SBS of ASTX+SEP, blood and TBXT+ASTX groups had significant differences from the SBS of the control group (p< 0.05). The ARI score of 0 had the highest frequency in the blood group. Conclusion: Due to the high coagulative effect of Astringedent X and acceptable SBS of Astringedent X in combination with GC-G Premio bond, this combination can be recommended for exposure of impacted teeth that are at high risk of blood contamination.